Pengelolaan Badan Usaha Milik Desa dan Hambatannya di Desa Menia Kecamatan Sabu Barat Kabupaten Sabu Raijua - Edon, Bernad; Yohanes, Saryono; Ratu Udju, Hernimus (Artemis Law Journal, 2024)
This paper aims to discuss to what extent the management of village-owned enterprises (BUMDes) in Menia Village, west Sabu District, Sabu Raijua Regency in realizing community welfare and to examine the inhibiting factors for managing village-owned enterprises (BUMDes) in Menia Village, west Sabu District, Sabu Raijua Regency. The research is Empiris juridical research, namely: to approach the problem under study with a real legal nature or by the reality experienced by the community. The research emphasizes the implementation and obstacles faced in carrying out the roles and functions of Village Owned Enterprises (BUMDes) in Menia Village, West Sabu District, Sabu Raijua. The results of this research show that the management of village-owned enterprises (BUMDes) in Menia Village is not running well and is not in accordance with the established rules. This is because the initial funds or capital for micro small businesses (kiosan) are smaller than the capital for social and other development in Menia villages. So the management of kiosk businesses experiences bottlenecks due to goods that have been purchased and resold by BUMDes members setting prices higher than market prices. The impact of this stalled kiosk business is making it difficult for people to meet their needs amidst activity restrictions (Covid-19) andd also losses in funds that have been provided by the the villagee for initial capital in running BUMDes. Inhibiting factors that occur in the management of BUMDes are divided into two parts, namely: human resources. Minimal budget, leadership, and governance, while the external factor was an unexpected disaster (COVID-19). This shows that in managing BUMDes there must be careful management and preparation so that the expected results can be achieved for the welfare of the Menia village community